Políticas Territoriais e Mobilidade Populacional na Amazônia: contribuições sobre a área de influência das Hidrelétricas no Rio Madeira (Rondônia/Brasil) - Maria Madalena de A. Cavalcante; Dorisvalder Dia Nunes; Ricardo Gilson da Costa Silva; Luiz Cleyton Holanda Lobato (Confins)
Population mobility in the Amazon is motivated by the search for new job opportunities, a fact linked to the structural changes, related to the action of the Federal Government through regional policies that have begun in the 60s and 70s. The implementation of projects of infrastructure establishes different functions and spatial re-structuring creating a new standard of social organization, cultural and economic. Currently, in Porto Velho, Rondônia, the construction of the hydroelectric of Jirau and Santo Antônio on the Madeira river, started in 2008, has been questioned about the new population flow, which can be characterized by two processes: the territorialization and deterritorialization. The first process is marked by attracting population, owing by labor supply and the second, guided by the deterritorialization because of population displacement in the reservoir area, presenting as the most critical case the Mutum-Paraná community, reaching all of its urban core. The aim of this paper is to evaluate the population mobility and the relationship between the deployment of infrastructure and exploitation of natural resources in the area of influence of dams. The methodology consists of the time-spatial analysis with literature review, fieldwork and geographic data collection in the area. The variables used were: population, main economic activities and rules of territory use (laws). These variables allowed us to understand the relationship between society and space in the process of organization and transformation. The analysis indicated that in this area, since their occupation until the present day, the population mobility has been driven by the implementation of works of infrastructure, appropriation and intensive exploitation of natural resources without economic stability, resulting in ebbs and flows of migrants.